1996
DOI: 10.1016/0014-5793(96)00879-4
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of insulin‐stimulated translocation of GLUT4 in single living cells visualised using green fluorescent protein

Abstract: Insulin increases glucose uptake by promoting the translocation of the GLUT4 isoform of glucose transporters to the plasma membrane. We have studied this process in living single cells by fusing green fluorescent protein (GFP) to the Nterminus (GFP.GLUT4) or C-terminus (GLUT4.GFP) of GLUT4. Both chimeras were expressed in a perinuclear compartment of CHO cells, and in a vesicular distribution through the cytosol. Insulin promoted an increase in plasma membrane fluorescence as a result of net translocation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 37 publications
2
43
1
Order By: Relevance
“…We have developed a novel system for monitoring GLUT4 trafficking in living single cells by taking advantage of the intrinsically fluorescent green-fluorescent protein (GFP) from Aequoria ictoria. We have previously demonstrated that expression of a chimaera between GLUT4 and GFP in Chinese hamster ovary cells allows us to follow insulin-stimulated GLUT4 translocation to the cell surface in living cells [16]. In the current study, we have continued the development of this system, such that we can follow GLUT4 movements in living 3T3 L1 adipocytes by time-lapse confocal microscopy.…”
Section: Introductionmentioning
confidence: 83%
“…We have developed a novel system for monitoring GLUT4 trafficking in living single cells by taking advantage of the intrinsically fluorescent green-fluorescent protein (GFP) from Aequoria ictoria. We have previously demonstrated that expression of a chimaera between GLUT4 and GFP in Chinese hamster ovary cells allows us to follow insulin-stimulated GLUT4 translocation to the cell surface in living cells [16]. In the current study, we have continued the development of this system, such that we can follow GLUT4 movements in living 3T3 L1 adipocytes by time-lapse confocal microscopy.…”
Section: Introductionmentioning
confidence: 83%
“…We therefore set out to examine the ability of GFP-Glut4 and Glut4-GFP to re-internalize from the plasma membrane after withdrawal of the insulin-stimulus (either by low pH washes, anti-insulin antibodies, or both) or in response to addition of inhibitors of PI3K, under similar conditions. In a previous study [28], we showed that a chimaera similar to GFP-Glut4 did not re-internalize from the plasma membrane after removal of the insulin stimulus, but that Glut4-GFP did. However, these data were collected using CHO cells, which are not a truely insulin-responsive cell line, and, moreover, the kinetics of internalization observed did not parallel those reported for endogenous Glut4.…”
Section: Figure 5 Gfp-glut4 Is Not Internalized After Insulin Withdrawalmentioning
confidence: 76%
“…After stimulation with insulin for 30 min as outlined above, cells were washed once with serum-free DMEM at 37 mC and then either : (i) incubated with anti-insulin antibodies in DMEM exactly as outlined in [28], or (ii) washed repeatedly in KRM buffer (as KRP, except that Hepes was replaced with 20 mM Mes, pH 6n0) on a hotplate at 37 mC for the times indicated in the Figure legends, prior to microscopic examination. In experiments where PI3K inhibitors were used, cells were washed in serum-free DMEM at 37 mC and incubated in serum-free DMEM containing either wortmannin (50-250 nM) or LY294002 (10 µM) in a CO # incubator for the times indicated.…”
Section: Insulin Reversal Experimentsmentioning
confidence: 99%
See 2 more Smart Citations